Design strategy for designing a service in Malaysia: a case study of automotive service center - Majid, Ahmad Zuhairi Abdul; Shaari, Nazlina (2010)
In the rapid development of new technologies, Malaysian has never left behind to experience new products and services. With new design thinking, principles and methods for service development will change the values of designers in education and creative industries suitable for the next generation. The understanding “dream society” of the next generation that will merge with the understanding of experience economy can build the service environment more sustainable. The new generation of mankind is looking for personal satisfaction with emotional value to their lives. This research will gives an allocation for industrial designers to play their role in helping the industry efficiently on quality concept of service design development in Malaysia. Result presented herein based on a survey and the scenario of Malaysian automotive service centers.